Studi Normatif Pendidikan Islam Multikultural - Isrofil Amar (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2010)
This paper basically argues that the many social problems that we are now faced are in fact product of the system of our religious education. The educational system of our Madrasas has not thus far shown its ability to address the spiritual needs of our students. This resulted in students absorbing the physical and at best the intellectual dimension of education by ignoring the moral and behavioral aspects of it. On this ground ?the paper argues- the system of our religious education must be revisited and reevaluated. Such system must not only indoctrinate students to learn about heaven, hell, what is lawful and lawful, belief and infidelity and the like, but must also teach them about tolerance, understanding and other social values. Our religious education must teach students conceptual knowledge but also educate them about how to respect others and live in a plural society. It is about these that this paper is concerned with. It is about the scheme of religious education for pluralism or multiculturalism.